Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 13

Answer

x = 4 y = 2

Work Step by Step

3x +2y = 16 x = 3y -2 Substitute x for 3y - 2 to the first equation. 3 ( 3y - 2 ) + 2y = 16 9y - 6 + 2y = 16 use the distributive property 11y - 6 + 6 = 16 + 6 simplify and add 6 to both sides 11y = 22 $\frac{11y}{11}$ = $\frac{22}{11}$ y = $\frac{22}{11}$ y = 2 x = $3\times2$ - 2 x = 6 - 2 x = 4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.